Effectiveness of Asthma Gymnastic on Levels of Tumor Necrosis Factor Alpha (TNF-α) in Asthma Patients - Andi Lis Arming Gandini; Joko Sapto Pramono; Umi Kalsum; Supriadi Supriadi; Azhari Azhari (Health Notions, 2020)
Asthma is a chronic inflammation of the airways that involves many cells and their elements. Non-pharmacological treatment of Asthma, one of them is Asthma Gymnastics. The purpose of this study was to determine the effect of asthma exercises on levels of Tumor Necrosis Factor Alpha (TNF-α) in asthma patients. This study used a quasi-experiment method of pre and post-test with control. The sample size of the intervention group was 8 people and the control group was 7 people. The results of hypothesis testing with the Wilcoxon Test found that there was an influence of asthma gymnastic intervention on the levels of Tumor Necrosis Factor Alpha (TNF-α) with a p-value of 0.046. The result of this study showed the effect of asthma exercises on levels of Tumor Necrosis Factor Alpha (TNF-α) in asthma patients. For further research, it is expected to research by increasing the number of treatments in the intervention group and controlling the drugs taken so that it is more optimal in its effect on respondents. Keywords: asthma; Tumor Necrosis Factor alpha (TNF-α); asthma gymnastics